2001
DOI: 10.14742/ajet.1790
|View full text |Cite
|
Sign up to set email alerts
|

A touch of sugar: A multimedia case study to facilitate student dietitians learning about the clinical management of diabetes

Abstract: This paper describes the development, implementation and evaluation of a multimedia case study on dietetic case management of diabetes. A multimedia web-based program was developed to use the interactive capacity of the web-based environment to enable student dietitians to develop the skills of clinical reasoning and to trigger their learning about the nutritional management of diabetes. A case study of a person with diabetes was developed using a simulated medical history, video clips and sound clips. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A total of 68 studies met the inclusion criteria and were included in this review . Fifty‐seven studies were identified from the search of 3779 records (Figure ) with an additional 11 studies identified through hand searching.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 68 studies met the inclusion criteria and were included in this review . Fifty‐seven studies were identified from the search of 3779 records (Figure ) with an additional 11 studies identified through hand searching.…”
Section: Resultsmentioning
confidence: 99%